NGURI-URI KEBUDAYAAN JAWA PADA PAKET PERNIKAHAN ADAT JAWA - Suharti, Suharti; Wibawa, Sutrisna; Widyastuti, Sri Harti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
The purposes of this program are (1) to motivate student becoming entrepeneurs at the Javanesse wedding traditional ceremony package, (2) to increase the students' entrepeneurship knowledge at the Javanesse wedding traditional ceremony, (3) to create connection between higher education, especially Javanesse Study Program of the Yogyakarta State Universty, and business partners of the Javanesse wedding traditional ceremony package, and (4) to increase the students' and the lectures' capabilities, skills, and practical experiences at  conducting of the Javanesse wedding traditional ceremony package. This  program  has  carried  out  at  three  stages,  those  are  (1)  an upgrading of the development of Javanesse wedding tradisional ceremony package, including MC materials, Javanesse speakers, the Javanesse cultural knowlege, the experiences of conducting wedding package, discussion and practice  of  determining  of the  package  and  suplying  clothing,  and  the knowladge of the entrepreneurship and business operational, (2) conducting of the training at Griya Rias Wijayaningtyas, and (3) work shop of structuring the wedding business plan and simulation of wedding ceremony pakcage. The result of this program are (1) all of the participants have motivation  to  wrestle  with  the  entrepreneurs of the  Javanesse  wedding package ompletely or partial, and as an individually or agroup, (2) all of the participants have busness operational plans at the Javanesse wedding package, (3) there is a conection between higher education, especially Javanesse Study Program of Yogyakarta State  University,  and  business partners of the Javanesse wedding traditional ceremony package, and (4) the participants of the  students and  the  lectures have  improved their skills, especially in practical skill of the Javanesse wedding ceremony